Modernization of Religious Teacher Professionalism Development in Indonesia - Junaidi Arsyad; Maisaroh Ritonga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Study aims to see the extent of modernization and development of the professional development of existing religious teachers. Of course, professional teachers who are proven by their competencies will encourage the realization of processes and performance products that can support improving the quality of Indonesian education. The method used in this study uses a qualitative research method with a descriptive analytical approach. Where this research approach seeks to explain a symptom, event or event that is happening at the present time where the researcher tries to photograph the events and events that are the center of attention and then describe what they are related to the term educator in the hadith review. The results of the study indicate that the Professionalism of Islamic Religious Education Teachers cannot be separated from three factors that are quite important, namely teacher competence, teacher certification, and teacher professional allowances. Teacher professionalism is a condition in which the work or activities carried out by a teacher become a source of income for life that requires expertise, proficiency, or skills that meet certain quality standards or norms and require professional education. Teacher's Professional and Career Guidance and Development (P3KG) includes the development of pedagogic competence, personality competence, social competence, and professional competence.